The Relation Between Chronic Diseases and Disability in Elderly of Amirkola - Seyed Reza Hosseini; Arezo Moslehi; Seyed Mohammadtaghi Hamidian; Seyed Alireza Taghian (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: There is an increase in the number of chronic diseases as the age increases. These diseases may not kill but they threaten the quality of life of patients and could lead to premature and severe disability. This study was done to determine the relation between chronic diseases and disability in activities of daily living in elderly in Amirkola.  Methods & Materials: This descriptive and cross-sectional study was done on older people in Amirkola. The data were collected using questionnaire including demographic characteristics and questions on disability (KATZ indexes). The data were analyzed using SPSS software and statistical tests such as chisquare, t-test and logistic regression. The p-value was P<0.05 and was considered as significant. Results: In this survey, 1017 older people were studied. 85% of them were independent in activity of daily livings (ADLs) and 15% of them were dependent. Stroke (OR= 7.2, CI=3.97-13.04, P<0.001), cancer (OR=6.80, CI=2.53-18.26, P<0.001) and hearing loss (OR=4.58, CI=3.01-6.98, P<0.001) had the most important role in causing disability. Women were more disabled than men in all ADLs and stroke (OR=10.12, CI=4.06-25.2, P<0.001), cancer (6.08, CI=1.29-28.6, P=0.022) and visual loss (4.26, CI=2.32-7.82, P<0.001) had the most impact on their quality of life. Conclusion: Our results indicate that chronic diseases and disability are more common among women and CVA, cancer, hearing loss and visual loss can have a negative effect on basic activities of daily living. Thus, appropriate interventions and plans for screening and reducing risk factors of these illnesses are necessary.